2019
DOI: 10.3906/sag-1712-166
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of mirror therapy and phantom exercises on phantom limb pain

Abstract: Background and aim: Although mirror therapy (MT) and phantom exercises (PE) have been shown to reduce pain, the efficacy of these methods in terms of pain, quality of life (QoL) and psychological status (PS) has not been investigated and compared to date. The aim of this study was to determine whether there is any difference between MT and PE in the treatment of phantom limb pain (PLP). Materials and methods: Forty unilateral transtibial amputees (aged 18-45 YR) participated in this study. Subjects were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
114
0
20

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(134 citation statements)
references
References 38 publications
0
114
0
20
Order By: Relevance
“…Five RCTs examining the efficacy of MT for PLP have been published over the past 5 years 20, 2124 . Sample sizes range from a total of 15 20 to 60 23 .…”
Section: Mirror Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Five RCTs examining the efficacy of MT for PLP have been published over the past 5 years 20, 2124 . Sample sizes range from a total of 15 20 to 60 23 .…”
Section: Mirror Therapymentioning
confidence: 99%
“…Sample sizes range from a total of 15 20 to 60 23 . Two studies 21, 22 recruited unilateral lower extremity amputees only (n = 85), one study 20 recruited unilateral upper limb amputees only (n = 15), and the remaining two studies 23, 24 recruited both unilateral lower (n = 60) and unilateral upper (n = 17) extremity amputees. Time since amputation ranged from less than 1 month 20 to 32 years 22 ; one study 23 did not report time since amputation.…”
Section: Mirror Therapymentioning
confidence: 99%
“…The reviewed studies in this systematic review also showed that the MBI had been widely used as an effective BOI toward a body part to reduce pain perception in patients with an amputation (Anaforoğlu Külünkoğlu et al, 2019;Chan et al, 2019;Darnall and Li, 2012;Diers et al, 2010;Finn et al, 2017;Kazemi et al, 2015;Ol et al, 2018;Ramadugu et al, 2017;Rothgangel et al, 2018;Tilak et al, 2016;Tung et al, 2014;Yildirim and Kanan, 2016). Indeed, the first clinical application of the MBI has been for pain relief in patients with phantom pain limb because of an amputation (Ramachandran et al, 1995).…”
Section: Bi To Modulate Pain Responsesmentioning
confidence: 84%
“…Twenty-four studies used BIs to reduce pain perception in clinical populations (Alphonso et al, 2012;Anaforoğlu Külünkoğlu et al, 2019;Chan et al, 2019;Choi et al, 2019;Darnall & Li, 2012;Diers et al, 2010;Finn et al, 2017;Giummarra, Fitzgibbon, et al, 2010;Hwang et al, 2014;Kazemi et al, 2015;Lopez-Carballo et al, 2018;Louw et al, 2017;Matamala-gomez et al, 2018;Ol et al, 2018;Ortiz-Catalan et al, 2016;Osumi et al, 2019;Pamment & Aspell, 2017;Ramadugu et al, 2017;Reinersmann et al, 2013;Rothgangel et al, 2018;Themelis & Newport, 2018;Tilak et al, 2016;Tung et al, 2014;Yildirim & Kanan, 2016) (see table 3). Particularly, twelve studies used the MBI in amputee patients suffering from phantom pain limb (Anaforoğlu Külünkoğlu et al, 2019;Chan et al, 2019;Darnall & Li, 2012;Diers et al, 2010;Finn et al, 2017;Kazemi et al, 2015;Ol et al, 2018;Ramadugu et al, 2017;Rothgangel et al, 2018;Tilak et al, 2016;Tung et al, 2014;Yildirim & Kanan, 2016). One study used the MBI with patients with chronic stroke to decrease neck pain discomfort (Choi et ...…”
Section: Results In Clinical Populationsmentioning
confidence: 99%
See 1 more Smart Citation